2014
DOI: 10.1063/1.4885195
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of silicon nanocrystals in a remote plasma without subsequent coagulation

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Especially on size distribution analysis, we have shown that, Raman spectroscopy is non‐destructive and time‐efficient, and gives reliable results as the analyses agree well with other size analysis techniques like TEM and PL. We indeed have shown that Raman spectroscopy helps us understand the growth mechanism and the formation region of Si‐NPs in plasmas by analyzing the size distribution of synthesized Si‐NPs with varying the plasma parameters …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Especially on size distribution analysis, we have shown that, Raman spectroscopy is non‐destructive and time‐efficient, and gives reliable results as the analyses agree well with other size analysis techniques like TEM and PL. We indeed have shown that Raman spectroscopy helps us understand the growth mechanism and the formation region of Si‐NPs in plasmas by analyzing the size distribution of synthesized Si‐NPs with varying the plasma parameters …”
Section: Resultsmentioning
confidence: 99%
“…In both of the pathways, further growth occurs via addition of the reactive species in the plasma leading to the formation of stable and fully crystalline Si‐NPs. During the nucleation, the growth reactions and atomic hydrogen association reactions occurring on the surface of the nanoparticle sustain crystallinity of Si‐NPs as a result of the energy released from these chemical reactions . In a controlled study of time modulated SiH 4 injection in the millisecond range, we have observed that the increase in the local density of SiH 4 does not increase the size of Si‐NPs produced, but it rather increases the number density of Si‐NPs and reduces the average size of these crystalline nanoparticles.…”
Section: Synthesis and Functionalization Of Si‐nps In Plasmasmentioning
confidence: 93%
See 2 more Smart Citations
“…18 If no stress is observed from XRD, direct analysis of size distribution can be performed from the asmeasured Raman spectrum. Since all the nanoparticles have stable structures, as observed previously, 14 the crystallinity is well established, and concerns related with poor crystalline structures are ruled out for the Raman analysis.…”
mentioning
confidence: 80%